PENERAPAN ULANGAN BERBASIS ANDROID UNTUK MENINGKATKAN KOMPETENSI GURU DI SMAN 1 BELIMBING KABUPATEN MELAWI - Daniati, Nia (Jurnal Pembelajaran Prospektif, 2020)
This study aims to improve the competence of Teachers of SMAN 1 Belimbing Melawi Regency. This research is a School Action Research. The subjects of this research were 28 teachers from SMA Negeri 1 Belimbing, consisting of 17 women and 11 men. Data collection techniques are done using questionnaires, interviews, observation sheets of teacher activities, notes and documentation. Analysis of the data used is descriptive qualitative. The results of this study indicate that the application of an Android-based test using Google form in the midterm and Midterm Assessments can improve teacher competency. This is seen based on the evidence of an increase in teachers who chieve understanding and can make questions based on android from pre-action, Cycle I and Cycle II. In cycle 1, as many as 21 teachers or 75% already understood the steps ofmaking test questions based on android then in the second cycle, as many as 27 teachers or 96.43% of teachers were able to apply android-based tests in the final semester evaluation effectively and efficiently